Obtaining glucosed syrups from husks of Banana (Musa paradisiaca L.) by enzymatic hydrolysis of cellulases - Decheco Egúsquiza, Alicia (2019)
The objective was to determine the effect of the application of the fungal cellulase enzyme on the silk banana peels (Musa paradisiaca) to obtain glucosed syrup. The enzymatic hydrolysis of banana shells at 30% (w / v) was studied at a constant temperature of 50 ° C. The independent variables to be controlled were the concentration of the fungal cellulase enzyme (0.5%, 1% and 1.5% w / v) and the hydrolysis time (18, 24 and 30 hours). The dependent variables were the percentage of Reducer Sugar and the percentage of Dextrose Equivalent (D.E.) of the enzymatically hydrolysed samples. The experimental design was completely randomized with factorial model 32. Glucosed syrups were obtained from silk plantain hulls by the enzymatic hydrolysis of the fungal cellulase. The highest percentages of Reducer Sugar and Dextrose Equivalent were presented in the Cellulase Concentration at 1.5% (w / v) during a hydrolysis time of 30 hours with average values ​​of 15.5% of reducing sugar percentage and 30.9% of percentage of Dextrose Equivalent. In the enzymatic hydrolysis with fungal cellulase at 1.5% (w / v) and 30 hours a higher value-added product was obtained, the operating conditions and the process steps were defined that should be adapted for the production of glucosed syrup from of banana peels (Musa paradisiaca).